2010
DOI: 10.5070/v424110353
|View full text |Cite
|
Sign up to set email alerts
|

Rodent Eradication on Cocos Island, Guam: Integrating Wildlife Damage Management, Resort Operations, and Non-Target Concerns

Abstract: Introduced Polynesian rats threatened native bird populations and forest habitat on Cocos Island, Guam. To eliminate the threat posed by rat populations, a rodent eradication was conducted on the 33.6-hectare off-shore island in March and April 2009. An integrated approach to eradication was implemented that included trapping, bait stations, and hand broadcast of rodenticide bait. Trapping was conducted within the resort buildings, where human activity precluded the use of rodenticides. Bait stations, employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…Although the 2009 eradication attempt on Lehua was not successful, the success of Mōkapu, along with numerous ground-based eradications that have used diphacinone around the world (e.g., Lujan et al 2010, Bell et al 2007 demonstrate that there is no intrinsic deficiency associated with using diphacinone for rat eradications. Rather, methods and regulatory restrictions need to be adjusted to accommodate an appropriate exposure profile for this compound and application method.…”
Section: Resultsmentioning
confidence: 99%
“…Although the 2009 eradication attempt on Lehua was not successful, the success of Mōkapu, along with numerous ground-based eradications that have used diphacinone around the world (e.g., Lujan et al 2010, Bell et al 2007 demonstrate that there is no intrinsic deficiency associated with using diphacinone for rat eradications. Rather, methods and regulatory restrictions need to be adjusted to accommodate an appropriate exposure profile for this compound and application method.…”
Section: Resultsmentioning
confidence: 99%
“…However, it must be noted that diphacinone is a first generation anticoagulant with lower toxicity and persistence than brodifacoum, which could explain the lack of residues on Mokapu and Lehua. Lujan et al (2010) reported that on Cocos Island, hermit crabs were sampled 7, 30, 60, and 90 days post-bait application. Brodifacoum residues were detected in one of 12 hermit crab samples, and diphacinone residues were not detected in any of the 12 hermit crabs.…”
Section: Discussionmentioning
confidence: 99%
“…Reintroduction attempts for one, the Guam rail or ko'ko' (Gallirallus owstoni), were attempted on Guam in areas depopulated of B. irregularis, but rails were extirpated by feral cats (Felis catus) (US Fish and Wildlife Service 2009). Cocos Island was a potential haven for Guam rail reintroduction due to absence of B. irregularis, feral cats, feral ungulates (Lujan et al 2010), and potential for removing other possible rail predators.…”
Section: Background and Problemmentioning
confidence: 99%